Go together : how the concept of Ubuntu will change how you live, work, and lead - Richards, Shola (Sterling Ethos, 2018)
"Workplace positivity expert Shola Richards (Making Work Work) explores a radical new concept for rethinking our personal, professional, and social lives: togetherness."--